Defining the origins of electron transfer at screen-printed graphene-like and graphite electrodes: MoO2 nanowire fabrication on edge plane sites reveals electrochemical insights. Issue 33 (4th August 2016) - Rowley-Neale, Samuel J.; Brownson, Dale A. C.; Banks, Craig E.
Abstract : The electrochemical fabrication of MoO2 nanowires onto the edge plane like-sites/defects of graphitic screen-printed electrodes reveals fundamental insights concerning the origin of electron transfer on carbon based materials. Abstract : Molybdenum (di)oxide (MoO2 ) nanowires are fabricated onto graphene-like and graphite screen-printed electrodes (SPEs) for the first time, revealing crucial insights into the electrochemical properties of carbon/graphitic based materials. Distinctive patterns observed in the electrochemical process of nanowire decoration show that electron transfer occurs predominantly on edge plane sites when utilising SPEs fabricated/comprised of graphitic materials. Nanowire fabrication along the edge plane sites (and on edge plane like-sites/defects) of graphene/graphite is confirmed with Cyclic Voltammetry, Scanning Electron Microscopy (SEM) and Raman Spectroscopy. Comparison of the heterogeneous electron transfer (HET) rate constants ( k °) at unmodified and nanowire coated SPEs show a reduction in the electrochemical reactivity of SPEs when the edge plane sites are effectively blocked/coated with MoO2 . Throughout the process, the basal plane sites of the graphene/graphite electrodes remain relatively uncovered; except when the available edge plane sites have been utilised, in which case MoO2 deposition grows from the edge sites covering the entire surface of the electrode. This work clearly illustrates the distinct electron transfer properties of edge and basal plane sites on graphitic materials, indicating favourable electrochemical reactivity at the edge planes in contrast to limited reactivity at the basal plane sites. In addition to providing fundamental insights into the electron transfer properties of graphite and graphene-like SPEs, the reported simple, scalable, and cost effective formation of unique and intriguing MoO2 nanowires realised herein is of significant interest for use in both academic and commercial applications.